Rising Prescription Drug Costs: What Is Involved and What Can Be Done? - Carroll, James (Maine Policy Review, 2003)
The rapid rise of prescription drug costs in the United States has triggered heated debate at the federal and state levels about how to control costs and expand access for those in need. In part, the United States finds itself in this situation because, unlike most countries throughout the world, the federal government thus far has refused to exact federal price restrictions on pharmaceutical products. James Carroll argues that this has left each state in the difficult position of trying to leverage lower costs and expanded access for its citizens. In this article, Carroll provides an overview of these attempts, including the Maine Rx program and the more recent legislation passed by Maine’s 121st legislature. He concludes with an analysis of how effective such programs are likely to be in the long run, particularly if the federal government continues to abdicate its responsibility to address the issue in comprehensive fashion.